Local market scale and the pattern of job changes among young men - Christopher H. Wheeler (W.E. Upjohn Institute for Employment Research, 2006)
In finding a career, workers tend to make numerous job changes, with the majority of 'complex' changes (i.e. those involving changes of industry) occurring relatively early in their working lives. This pattern suggests that workers tend to experiment with different types of work before settling on the one they like best. Of course, since the extent of economic diversity differs substantially across local labor markets in the U.S. (e.g. counties and metro areas), this career search process may exhibit important differences depending on the size of a worker's local market. This paper explores this issue using a sample of young male workers drawn from the National Longitudinal Survey of Youth 1979 Cohort. The results uncover two rather striking patterns. First, the likelihood that a worker changes industries rises with the size and diversity of his local labor market when considering the first job change he makes. Second, however, this association gradually decreases as a worker makes greater numbers of job changes. By the time he makes his fourth change, the likelihood of changing industries significantly decreases with the scale and diversity of the local market. Both results are consistent with the idea that urban areas play an important role in the job matching process.
Keywords: J24; R23; 330; Job Search; Labor Market Matching; Agglomeration; Arbeitsmarkt; Arbeitsuche; Matching; USA